SOCIAL REINTEGRATION PROGRAM FOR PRISONERS IN CLASS IIA SERANG PRISON - Ahmad Ali Nur Saidi; Ahmad Fajri Aslam; Daniel Lukman Sipahutar (Journal of Management Small and Medium Enterprises (SME's), 2025)
The Indonesian correctional system has shifted from a retributive to a rehabilitative approach, aiming to rehabilitate inmates so they can reintegrate into society. Social reintegration plays a crucial role in this process but faces challenges such as social stigma, limited facilities, and inmates' lack of preparedness. This study aims to analyze the effectiveness of the Social Reintegration Program at Class IIA Serang Prison, focusing on correctional stages, implementation barriers, and improvement strategies. The research employs a qualitative descriptive approach, utilizing interviews, observations, and document studies. Findings reveal that the program follows four key stages: admission and orientation, advanced personality development, assimilation, and community integration. While the program positively impacts inmates’ readiness to rejoin society, challenges remain, including limited training facilities, lack of community support, and inadequate post-release supervision. The study concludes that social reintegration can be more effective with enhanced training facilities, increased public awareness, and strengthened post-release assistance by the Correctional Center (Bapas).